Analisis Tata Kelola It Menggunakan Framework Cobit 5 Pada Domain Monitor, Evaluate And Assess (Mea) - Bram Sivadjati; Thamrin Sofian; Ferdy Achmad Zulfikar; Richardus Eko Indrajit; Erick Dazki (Universitas Pradita, 2021)
Nowadays information and technology (IT) plays an important role in the organization in order to support the organization to be more productive and as a result become advanced organization. In fact, the organizations like; logistic, education and shopping center have used IT to support their business system. However, as a matter of fact the use of the IT in their organizations still need in-depth evaluation. Therefore, COBIT framework version 5 will be used in this study in evaluating with the intention of gathering some information about IT govermance in related industries especially in MEA (Monitor, Evaluate, and Assess) domain. The result of the evaluation can be used as a recommendation of each industries to have a better IT govermance in the future.